(untitled) (aSSIST Business Review, 2026)
(1) Background/Purpose: The Korean coffee market surpassed 7 trillion KRW in 2023, with low-cost coffee franchises emerging as a dominant force. This study investigates the competitive success strategies of these franchises, focusing on Compose Coffee in comparison with MegaMGC Coffee, The Venti, and Ten Percent Coffee. (2) Methodology: Marketing strategies were analyzed using the 4P (Product, Price, Place, Promotion) and STP (Segmentation, Targeting, Positioning) frameworks, drawing on annual reports, company websites, industry databases, and news sources for each brand. (3) Findings: Compose Coffee achieved outstanding performance—with a 41.3% operating margin in 2023 and 2,732 franchise stores—through vertical integration of its own roasting facility, an aggressive low-price strategy anchored at 1,500 KRW for iced Americano, star marketing (BTS’s V), and a digital platform surpassing 17 million app members. Other brands pursued distinct approaches: MegaMGC Coffee emphasized large-volume value drinks; The Venti cultivated a trendy, youth-oriented premium image; Ten Percent Coffee positioned around quality-price balance and ESG. (4) Originality/Value: This is one of the first comparative studies to apply both 4P and STP frameworks simultaneously across four leading Korean low-cost coffee franchises. Practical strategic recommendations are offered for brand differentiation, pricing, quality management, digital marketing, sustainable management, and innovation adaptability.